Interpersonal influence : two characterisations - Ngiam, Li Yi (2018)
In this paper, I attempt to provide a comprehensive picture of interpersonal influence that can serve as the groundwork for future discussions on issues related to influence. I conclude that there are two characterisations that work in tandem to provide this comprehensive picture. The first characterisation pertains to how we understand interpersonal influence in the abstract — interpersonal influence refers to the psychological process within one where another’s action(s) or product(s) contributes to the formation of (a) motivating reasons(s) in him/her. The second characterisation includes the standard of what one takes to be significant, to reflect how interpersonal influence is concretely understood when it comes to recognising concrete occurrences of influence. In this second characterisation, interpersonal influence refers to the psychological process within one where another’s action(s) or product(s) contributes to the formation of (a) motivating reason(s) in him/her, and where the occurrence of this process and/or the resultant acting is deemed by one to be significant to him/her.